A new testing protocol for zirconia dental implants. Issue 1 (January 2015) - Sanon, Clarisse; Chevalier, Jérôme; Douillard, Thierry; Cattani-Lorente, Maria; Scherrer, Susanne S.; Gremillard, Laurent
Abstract: Objectives: Based on the current lack of standards concerning zirconia dental implants, we aim at developing a protocol to validate their functionality and safety prior their clinical use. The protocol is designed to account for the specific brittle nature of ceramics and the specific behavior of zirconia in terms of phase transformation. Methods: Several types of zirconia dental implants with different surface textures (porous, alveolar, rough) were assessed. The implants were first characterized in their as-received state by Scanning Electron Microscopy (SEM), Focused Ion Beam (FIB), X-Ray Diffraction (XRD). Fracture tests following a method adapted from ISO 14801 were conducted to evaluate their initial mechanical properties. Accelerated aging was performed on the implants, and XRD monoclinic content measured directly at their surface instead of using polished samples as in ISO 13356. The implants were then characterized again after aging. Results: Implants with an alveolar surface presented large defects. The protocol shows that such defects compromise the long-term mechanical properties. Implants with a porous surface exhibited sufficient strength but a significant sensitivity to aging. Even if associated to micro cracking clearly observed by FIB, aging did not decrease mechanical strength of the implants. Significance: As each dental implant company has its own process, all zirconia implants may behave differently, even if the starting powder is the same. Especially, surface modifications have a large influence on strength and aging resistance, which is not taken into account by the current standards. Protocols adapted from this work could be useful.